Reference gene selection for quantitative real-time RT-PCR normalization in Clarias magur at different larval developmental stages - MIR, ISHFAQ NAZIR; SRIVASTAVA, P P; BHAT, I A; MURALIDHAR, A P; P, GIREESH-BABU; VARGHESE, TINCY; CHANU, THONGAM IBEMCHA; JAIN, K K (The Indian Journal of Animal Sciences, 2018)
Reference genes employed for normalizing quantitative PCR data are important for the accurate analysis of gene expression. To date, no reference genes have been screened for developmental gene expression studies in Clarias magur. In the present study, three commonly used and constitutively expressed genes viz. beta actin (β- actin), glyceraldehyde-3-phosphate dehydrogenase (GAPDH) and elongation factor-alpha 1 (EFa1) were examined for their efficacy as internal control to avoid any variation during qRT-PCR expression analysis at different developmental stages of C. magur. All the selected housekeeping genes showed a variable level of mRNA expression during the developmental stages of C. magur. Using three independent statistical algorithms (delta-CT, BestKeeper and NormFinder), β-actin and GAPDH were identified as the suitable genes at different developmental stages. However, comprehensive gene stability evaluation denoted β-actin to be the most stable gene for carrying any gene expression studies. The present results, recommend β-actin as the optimal housekeeping gene for qRT-PCR analysis during different developmental stages of C. magur.